2015
DOI: 10.1002/ps.4061
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain alkanes synergise responses of moth pests to their sex pheromones

Abstract: The findings show the promise of using short-chain alkanes as pheromone synergists for mating disruption of insect pests of food crops. Alkane-pheromone combinations are expected to increase the competitiveness of dispensers with females, and to reduce the amount of pheromone needed for the control of these pests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…For example, in the corn earworm Helicoverpa zea , simultaneous application of plant odorants with the major sex pheromone component of the moth increases the firing rate of pheromone-responsive OSNs in males, although those neurons do not respond to stimulation with plant odorants separately (Ochieng et al, 2002 ). Moreover, in beetles (Nakamuta et al, 1997 ) and many lepidopteran species (Dickens et al, 1993 ; Light et al, 1993 ; Reddy and Guerrero, 2000 ; Deng et al, 2004 ; Namiki et al, 2008 ; Schmidt-Büsser et al, 2009 ; Gurba and Guerin, 2015 ) the behavioral response is also increased when plant compounds are combined with the corresponding pheromone components. In contrast, a variety of studies demonstrated that pheromone detection can also be inhibited by interactions with plant odorants (Den Otter et al, 1978 ; Kaissling and Bestmann, 1989 ; Pophof and Van Der Goes Van Naters, 2002 ; Party et al, 2009 , 2013 ; Hillier and Vickers, 2011 ; Chaffiol et al, 2012 ; Deisig et al, 2012 ; Pregitzer et al, 2012 ; Hatano et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the corn earworm Helicoverpa zea , simultaneous application of plant odorants with the major sex pheromone component of the moth increases the firing rate of pheromone-responsive OSNs in males, although those neurons do not respond to stimulation with plant odorants separately (Ochieng et al, 2002 ). Moreover, in beetles (Nakamuta et al, 1997 ) and many lepidopteran species (Dickens et al, 1993 ; Light et al, 1993 ; Reddy and Guerrero, 2000 ; Deng et al, 2004 ; Namiki et al, 2008 ; Schmidt-Büsser et al, 2009 ; Gurba and Guerin, 2015 ) the behavioral response is also increased when plant compounds are combined with the corresponding pheromone components. In contrast, a variety of studies demonstrated that pheromone detection can also be inhibited by interactions with plant odorants (Den Otter et al, 1978 ; Kaissling and Bestmann, 1989 ; Pophof and Van Der Goes Van Naters, 2002 ; Party et al, 2009 , 2013 ; Hillier and Vickers, 2011 ; Chaffiol et al, 2012 ; Deisig et al, 2012 ; Pregitzer et al, 2012 ; Hatano et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%